2022
DOI: 10.1101/2022.03.04.482898
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A mass spectrometry-based atlas of extracellular matrix proteins across 25 mouse organs

Abstract: The extracellular matrix is a critical non-cellular component of multi-cellular organisms containing a variety of proteins, glycoproteins, and proteoglycans which has been implicated in a wide variety of essential biological processes, including development, wound healing, and aging. Due to low solubility, many ECM proteins have been underrepresented in previous proteomics datasets. Using an optimized 3-step decellularization and ECM extraction method involving chaotrope extraction and digestion via hydroxylam… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
(53 reference statements)
0
17
0
Order By: Relevance
“…The core matrisome includes collagens, ECM glycoproteins and proteoglycans, whereas the matrisomeassociated proteins are composed of ECM-affiliated proteins, ECM regulators and secreted factors. Very recently, McCabe et al reported an extensive mouse ECM atlas 6 based upon the characterization of the ECM profiles of 25 organs by liquid chromatography-tandem mass spectrometry (LC-MS/MS) [13].…”
Section: Introductionmentioning
confidence: 99%
“…The core matrisome includes collagens, ECM glycoproteins and proteoglycans, whereas the matrisomeassociated proteins are composed of ECM-affiliated proteins, ECM regulators and secreted factors. Very recently, McCabe et al reported an extensive mouse ECM atlas 6 based upon the characterization of the ECM profiles of 25 organs by liquid chromatography-tandem mass spectrometry (LC-MS/MS) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of tissue samples was performed as previously described. 19 Briefly, 5 mg of lyophilized tissue samples were processed by a stepwise extraction with CHAPS and high salt, guanidine hydrochloride and chemical digestion with hydroxylamine hydrochloride (HA) in Gnd-HCl generating cellular, soluble ECM (sECM), and insoluble ECM (iECM) fractions for each sample, respectively. Protein concentration of each fraction for each sample was measured using A660 Protein Assay (Pierce™).…”
Section: Methodsmentioning
confidence: 99%
“…Liquid chromatography mass spectrometry (LC-MS/MS) was performed using an Easy nLC 1200 instrument coupled to a Orbitrap Fusion Lumos Tribrid mass spectrometer (all from ThermoFisher Scientific) as previously described. 19 Fragmentation spectra were searched against the UniProt Mus musculus proteome database (Proteome ID # UP000000589 downloaded 1 December 2021) using the MSFragger-based FragPipe computational platform. 21 Contaminants and reverse decoys and were added to the database automatically.…”
Section: Methodsmentioning
confidence: 99%
“…A recently published mass-spectrometry atlas of the matrix in 25 different organs confirmed very similar composition of matrix proteins across different organs with tissue-specific differences in protein abundances. 66 The glomerular matrisome contains comparatively higher abundance of basement membrane components; type IV collagen α4, laminin β2, agrin and nidogen-1; whereas the TI matrix showed enrichment for other structural proteins such as von Willebrand factor and EMILIN-2. Whilst the main function of the TI is forming a scaffold around tubules, the glomerular matrix organizes into the mesangial matrix and the glomerular basement membrane, which forms an integral part of the glomerular filtration barrier.…”
Section: The Tubulointerstitial Matrix In Health and Diseasementioning
confidence: 99%